Perception of Extension Officials on Technology Adoption by Rural Farmers in Omusati Region of Namibia - Togarepi, C.; angula, M.; Thomas, B. (Namibian Journal for Research, Science and Technology, 2018)
Agricultural production in northern Namibia is affected by erratic rainfall, low soil fertility, limited access to credit, pest and disease incidences as well as limited use of new agricultural innovations. Despite efforts by the government to increase farmers’ productivity, adoption rate of modern innovations is however, still very low among rural farmers. The purpose of this study is to find out the perceptions of the agricultural extension officials on the technology adoption by the farmers in Omusati region. The research questions focused on soliciting information on perceptions of extension officials on agricultural innovations among rural farmers. A purposive sampling method was used to collect data from agricultural extension officials using a structured questionnaire. The data was analysed using frequencies and cross tabulations for descriptive statistics. The results indicate that most public extension officials feel that they are not specialised in all areas that they need to assist farmers in, area of jurisdiction is too large, and the allowable kilometres for visiting farmers are too low. Furthermore, the results showed that farmers do not attend meetings, farmers fail to follow instructions, farmers lack interest in new technology, extension officials are not adequately trained on new innovations and have too much administrative work among others. The study concluded that the extension officials perceive technology adoption among rural farmers to be moderate (average) due to both extension officials and farmers’ related factors such as farmers not following instructions and farmers not attending meetings where information on technology is shared. The study thus recommends that there is need for training of extension officials on new technology use, hiring more extension officials, hiring office assistants to assist with office administrative work and create awareness among farmers on aspects that can enhance technology adoption by farmers.